Podcasts as an Innovative Solution for Teaching Arabic: Enhancing Speaking and Listening Skills - Habib, Moh. Tohiri; Hanifansyah, Nur; Solehudin, Muhamad; Mahmudah, Menik; Syakur, Sultan Abdus (Universitas Yudharta Pasuruan, 2024)
In the modern era of digital education, podcasts have emerged as a dynamic medium to address the gaps in traditional Arabic language teaching, particularly in listening (maharah istima’) and speaking (maharah kalam) skills. Recognizing the challenges of limited exposure to authentic language environments and traditional methods that often fail to engage learners, this study aims to evaluate the effectiveness of podcasts as a pedagogical tool for Arabic language instruction. A qualitative research design was employed, involving 20 advanced-level students (santri) aged 16–18 from Darullughah Wadda’wah, a renowned Islamic boarding school. Participants engaged with curated Arabic podcasts over four weeks, supplemented by group discussions, structured speaking exercises, and comprehension assessments. Data collection included pre- and post-tests, observational notes, audio recordings, and semi-structured interviews. Results indicate a significant improvement in listening skills (30%) and speaking proficiency (25%), with students reporting enhanced vocabulary retention and increased confidence in communication. Observational data highlighted elevated engagement and motivation during podcast-based learning compared to traditional approaches. This study concludes that podcasts are a versatile and innovative medium for fostering language skills, bridging theoretical and practical knowledge gaps. Recommendations include expanding podcast topics and integrating visual aids for broader applicability in diverse educational contexts.